MANAJEMEN KONFLIK PADA SATUAN POLISI HUTAN REAKSI CEPAT (SPORC) BRIGADE BERUANG DI PROVINSI RIAU - Sibarani, Ryandi Martohonan; Tua R.F.S, Harapan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Conflict in an organization is a difference that arises between two parties or more objects being contested. and in the organization, conflicts often occur frequently because the difference in taking a decision and taking an action in the organization. As one of the organizations in the forestry sector, SPORC must required to think quickly, and act appropriately in tackling problems especially in the forestry sector.The Purpose of this research is to know and analyze how the conflict management of the Forestry Police High-Speed Squad (SPORC) of Brigade Beruang Riau Province and also the factors which influencing that conflict Management. This research is using a research-qualitative method which it'd explore the problem ,Identify causes of factors, and Composing theory which it has basically investigate. The theory of this research is Theory of Conflict Management by Wirawan with Three Indicators of Conflict Managament. And the technical analyze data using qualitative method.After the research it found that Conflict Management at Forestry Police High-Speed Squad (SPORC) Of Brigade Beruang Riau Province causes by Focussing to Vision, Mission, and Goals of Organization, Facilitating realization of activity, and Increasing Decision through Opinions. and the factors of incluiding conflict is : Integrity, Technical Ability, and Interaction.Keyword: Conflict Management,Conflict Management in Organization